Synthesis, Crystal Structure and Catalytic Activity of Tri-Nuclear Zn(II) Complex Based on 6-Phenylpyridine-2-carboxylic Acid and Bis(4-pyridyl)amine Ligands - Li-Hua Wang; Fan-Yuan Kong; Tai Xi-Shi (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2022)
A new trinuclear Zn (II) complex, [Zn3(L1)4(L2)2(CH3COO)2] (1) (HL1 = 6-phenylpyridine-2-carboxylic acid, L2 = bis(4-pyridyl)amine) has been synthesized by 6-phenylpyridine-2-carboxylic acid, NaOH, bis(4-pyridyl)amine and Zn(CH3COO)2•2H2O. The complex 1 has also been structural characterized by elemental analysis and single crystal X-ray diffraction. The results reveals that complex 1 is made up of three Zn(II) ions, four L1 ligands, two L2 ligands and two CH3COO- anions. In 1, both Zn1 ion and Zn1a ion are five-coordinated with two O atoms from two different L1 ligands, two N atoms from two different L1 ligands, and one N atoms from bis(4-pyridyl)amine ligand, respectively, and forms a distorted trigonal biyramid geometry. And Zn2 ion is four-coordinated with two O atoms from two different CH3COO− anions and two N atoms from two different L2 ligands, forming a distorted tetrahedral geometry. Complex 1 displays a 3D network structure by the intermolecular N−H···O hydrogen bonds. The catalytic performance for oxidation of benzyl alcohol with O2 was studied under mild reaction conditions using complex 1 as catalyst. The results demonstrated that the catalysts were very active, and the yield of benzaldehyde was 50.8% at 90 °C with THF as solvent under 0.5 MPa O2 within 3 h. Copyright © 2022 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).